Numerical Modelling of the Acoustic Pressure Inside an Axisymmetric Lined Flow Duct - TAKTAK, Mohamed; MAJDOUB, Mohamed Ali; BENTAHAR, Mabrouk; HADDAR, Mohamed (Archives of Acoustics, 2012)
Numerical methods are mostly used to predict the acoustic pressure inside duct systems. In thispaper, the development of a numerical method based on the convected Helmholtz equation to computethe acoustic pressure inside an axisymmetric duct is presented. A validation of the proposed method wasdone by a comparison with the analytical formulation for simple cases of hard wall and lined ducts. Theeffect of the flow on the acoustic pressure inside these ducts was then evaluated by computing this fieldwith different Mach numbers.